Improved coordinated control strategy for VSC-MTDC system with DC voltage secondary regulation - Li, Congshan; Zhang, Xiaowei; He, Ping; Zhao, Kefeng; Liu, Libing (Frontiers in Energy Research, 2024)
Droop control is widely used in multi-terminal flexible DC (VSC-MTDC) transmission systems by virtue of the advantage of multi-station cooperative unbalanced power dissipation, however, the essence of the droop control strategy is to change the DC current to realize the unbalanced power dissipation, and the resulting DC voltage deviation will affect the normal operation of the system. Firstly, this paper theoretically analyses the working characteristics of the conventional droop control and proposes a control method to realize the quasi-differential-free regulation of DC voltage by translating the droop curve. Second, according to the power margin of the converter station, the feedforward compensation amount of each converter station is reasonably set to avoid the power impact on the converter station. Finally, for the problem that the actual value of DC voltage still deviates from the rated value, a control strategy containing secondary regulation of DC voltage is proposed to further restore the DC voltage to the initial value on the basis of ensuring the effect of power regulation, which improves the stability of the operation of the VSC-MTDC system. The final simulation results verify the effectiveness of the proposed method.